Association Between Telomere Length and Skin Cancer and Aging: A Mendelian Randomization Analysis - Son, Nannan; Cui, Yankun; Xi, Wang (Frontiers in Genetics, 2022)
Background: Telomere shortening means cell senescence. However, this telomere length (TL)-related cellular senescence has opposite effects in different cancers, resulting in a paradoxical relationship between senescence and cancer. We used an epidemiological observation of the association between TL and skin cancer and aging to explore whether such a rebuttal exists in skin tissue. Methods: This study employed two-sample Mendelian randomization (MR) to analyze the causal relationship between TL and skin cancer (melanoma and non-melanoma skin cancers [NMSCs]). We studied single nucleotide polymorphisms (SNPs) obtained from pooled data from genome-wide association studies (GWAS) in the literature and biobanks. Quality control was performed using pleiotropy, heterogeneity, and sensitivity analyses. Results: We used five algorithms to analyze the causal relationship between TL and skin aging, melanoma, and NMSCs and obtained consistent results, such as the MR Egger score. TL shortening reduced NMSCs and melanoma susceptibility risk with a specific odds ratio (ORs) of 1.0344 (95% confidence interval (CI) 1.0168-1.0524, p < 0.05) and 1.0127 (95% CI 1.0046-1.0209, p < 0.05), respectively. Conversely, TL shortening was validated to increase skin aging probability (OR = 0.96, 95% CI 0.9332-0.9956, p < 0.05); MR Egger, maximum likelihood and inverse variance weighted (IVW) found significant heterogeneity among instrumental variables (IV) estimates identified as MR-Egger Q = 76.72, p < 0.01. The leave-one-out analysis also showed that the SNP sensitivity was robust to each result. Conclusion: This study supported the causal relationship that TL shortening may promote skin aging development and reduce the risk of cutaneous melanoma and NMSCs. The results provide a reference for future research on the relationship between skin aging and cancer in clinical practice.